Ethnic and Environmental Differences in Various Markers of Dietary Intake and Blood Pressure among Chinese Han and Three Other Minority Peoples of China: Results from the WHO Cardiovascular Diseases and Alimentary Comparison (CARDIAC) Study - DING, Yuan; SUN, Shinfu; YAMORI, Yukio; LIU, Lisheng; ZHANG, Hongxiu; MIZUSHIMA, Shunsaku; ZHAO, Guangsheng; HE, Bingxian; IKEDA, Katsumi; MIKI, Tomohiro; LIU, Longjian; NARA, Yasuo; et al. (Hypertension Research, 2001)
Our aim was to examine differences in dietary intake and blood pressure (BP) and their associations in four different ethnic Chinese populations, the Han, the Uygur, the Kazak and Tibetan subjects. This study used a sub-database of the Chinese sample of the WHO-Cardiovascular Diseases and Alimentary Comparison (CARDIAC) Study. The WHO-CARDIAC Study was a multicenter cross-sectional study. In each center, 100 men and 100 women aged 48-56 years were selected at random from the local population. Various markers of dietary intake and their relation with BP were studied. The results of the present study indicated the following. 1) There were significant differences in mean BP and prevalence rates of hypertension, with both being higher in the Kazak and Tibetan subjects than in Han and Uygur subjects. 2) The highest mean body mass index (BMI) was observed in the Kazak subjects, while the highest 24-h urinary sodium (Na) and sodium to potassium (Na/K) ratio excretion were observed in the Tibetan subjects. There were also significant differences in other factors, such as magnesium, 3-methylhistidine (3MH)(a biological marker of animal protein intake) and taurine (a biological marker of seafood intake) excretion levels among the four ethnic peoples. 3) In general, BMI, Na and/or Na/K ratios were positively, and 3MH/creatinine and taurine/creatinine ratios were negatively associated with BP. 4) After adjustment for age, sex and potassium, subjects with obesity (BMI≥26 kg/m2) had significantly higher relative risk of being hypertensive (HT) than those with BMI<26 kg/m2 in the Han, Uygur and Kazak populations; and subjects with elevated sodium excretion (Na≥244 mmol/day) had significantly higher relative risk of being HT than those with Na<244 mmol/day in the Han, Uygur and Tibetan populations. In conclusion, mean BP and prevalence rates of hypertension were significantly different among the four ethnic groups. These differences are likely to be due, at least in part, to the differences in several diet-related factors, which in turn are associated with culture and environmental differences. Different health promotion strategies might thus be emphasized in different populations. (Hypertens Res 2001; 24: 315-322)